Enhancing creativity in group collaboration: How performance targets and feedback shape perceptions and idea generation performance. (January 2015) - Wang, Xuequn; Schneider, Christoph; Valacich, Joseph S.
Highlights: Our study demonstrates the importance of satisfying people's need for competence. Challenging performance targets can lower perceived competence. The effect of a challenging target is stronger with controlling feedback. Abstract: As Information and Communication Technologies (ICTs) have become established tools for communication, organizations increasingly use computer-mediated work groups to support various business processes and find creative solutions to organizational problems. In such a context, groups' creative performance can greatly contribute to organizational success. Previous literature has examined the influence of various factors on different outcomes of group collaboration. However, mechanisms through which creativity can be improved, and how to design ICT's interfaces to increase creativity have received little attention. In this study, we aim to understand the effects of two specific motivational affordances, namely, performance targets and performance feedback, on people's perceived competence and creativity within the context of computer-mediated collaboration. Using computer-mediated idea generation as an instantiation of collaboration systems, we test the effects of performance targets and different types of feedback on people's perceived competence and creativity in a controlled laboratory experiment. Our results show that the difficulty of performance targets and the type of performance feedback interact, influencing people's perceived competence, which in turn influences their creativity in group collaboration. We conclude our study with a discussion of implications for the design of human–computer interfaces for computer-mediated idea generation.